Morfologia externa de Triatoma ryckmani Zeledón & Ponce, 1972 vista através da microscopia eletrônica de varredura External morphology of Triatoma rickmani Zeledón & Ponce, 1972 by scanning electron microscopy - Rodolfo U Carcavallo; Rodrigo Zeledón; José Jurberg; Itamar Galindez (Memorias do Instituto Oswaldo Cruz, 1996)
A male of Triatoma ryckmani Zeledón & Ponce, 1972, was studied by scanning electron microscopy. Only few specimens of this species are known. In this paper, some structures from the head, thorax, abdomen and distal region of the second leg are shown. Some of them could have taxonomic importance, as the oculo-ocellar region, the buccula, the anterolateral angle of the collar, the scutellum with the process longer than the main body, the stridulatory sulcus with an unusual backward vermiform area, and the tibia-tarsal articulation, with a spongy fossula. The last structure was absent in specimens previously studied (Lent & Wygodzinsky 1979). Differences between this specimen and others previously described by several authors are dicussed.